Sense of courage: The mediating role of courage between emotional reflexivity and work-life integration among nurses in Indian hospitals - Lalatendu Kesari Jena; Jeeta Sarkar; Saumya Goyal (Elsevier, 2021)
Objectives: This study aimed to determine the relationship between emotional reflexivity and work-life integration through the mechanism of moral courage and enhance our understanding of the importance of these nursing concepts to enable the nurses to develop better coping strategies for work-life integration. Methods: A cross-sectional survey was performed with 249 nurses, including staff nurses, ICU and critical care nurses, operation theatre nurses, pediatric nurses from 17 hospitals. Emotional Reflexivity, work-life integration, and courage were measured using a demographic information questionnaire, Life Project Reflexivity Scale (LPRS), Nurse's Moral Courage Scale (NMCS), and Work-Life Boundary Enactment (WLBE) scale. A series of multiple regressions analyzed the mediating effect. Results: Emotional Reflexivity was positively correlated with work-life integration (β = 0.66, P < 0.01). There was a positive correlation between emotional reflexivity and moral courage. But the path did not get the necessary support in the structural equation modeling (SEM) (β = −0.13, P = 0.40). When controlling for courage (β = 0.42, P < 0.01), the association was significant between emotional reflexivity and work-life integration with partial mediation. Conclusion: The study reported a positive correlation between reflexivity and work-life integration. Thus, nurses' work-life integration becomes better by reinforcing their emotional reflexivity and moral courage.